Fear of Missing out and Online Social Anxiety in University Students: Mediation by Irrational Procrastination and Media Multitasking - Weimiao Wu; Jie Zhang; Namjeong Jo (Behavioral Sciences)
With the rapid growth of internet mobile technology, recent research has increasingly focused on the mental health challenges faced by young people, particularly in relation to social media use. One significant concern is the impact of the fear of missing out (FoMO) and online social anxiety, yet the underlying mechanisms that link these factors remain largely unexplored. This study aims to address this gap by investigating the role of FoMO in predicting online social anxiety among university students, with a particular focus on understanding how irrational procrastination and media multitasking may mediate this relationship. In total, 451 university students completed a survey on demographics, FoMO, online social anxiety, irrational procrastination, and media multitasking questionnaires. After controlling for demographic variables, the findings revealed that (a) FoMO showed a significant positive correlation with online social anxiety; (b) the connection between FoMO and online social anxiety in university students was partially mediated by irrational procrastination; and (c) the connection between FoMO and online social anxiety in university students was partially mediated by media multitasking. This research contributes to the understanding of the psychological mechanisms that link FoMO to online social anxiety, offering insights that can inform interventions aimed at improving university students’ mental health in the digital age.